Identifying Learning Obstacles in Pre-Service Mathematics Teachers' Understanding of Circle Concepts: A Preliminary Study within A Didactical Design Research Framework - Febrianti, Tri Sedya; Fatimah, Siti; Dahlan, Jarnawi Afgani (FKIP Universitas Lampung, 2024)
Identifying Learning Obstacles in Pre-Service Mathematics Teachers' Understanding of Circle Concepts: A Preliminary Study within A Didactical Design Research Framework. Objective: This research aims to identify the types of learning obstacles that pre-service mathematics teachers encounter when solving problems related to circles. Methods: A qualitative research approach with a case study design was employed to obtain in-depth information regarding the learning obstacles faced by pre-service mathematics teachers. This involved administering a written test on circle material and conducting in-depth interviews using an interview guide to explore the participants' responses. Findings: The research was conducted from May 21 to June 14, 2024, at a national university in Java, Indonesia. The participants included 33 pre-service mathematics teachers enrolled in the Flat Analytical Geometry course (2nd semester) who had been exposed to circle material. While almost all 33 participants were able to provide answers, they were not always completely correct. The analysis focused on 8 participants selected for data confirmability through in-depth interviews. The diversity of learning obstacles (LOs) found among these 8 participants was representative of the LOs identified in the test results of all participants. The results indicate that all pre-service mathematics teachers experienced learning obstacles in solving circle-related problems. The study identified all three types of learning obstacles ontogenic, epistemological, and didactical among the participants. In summary, pre-service mathematics teachers face ontogenic, epistemological, and didactical learning obstacles when solving circle problems. Conclusion: The analysis of learning obstacles, which is part of Didactical Design Research (DDR), was conducted in this study. The results of this research can serve as a reference in creating learning designs that minimize learning obstacles related to the circle material experienced by pre-service mathematics teachers. Keywords: learning obstacles, pre-service, mathematics teachers, circle, DDR. DOI: http://dx.doi.org/10.23960/jpmipa/v25i1.pp419-439